Applicability of Talent Management with Special Reference to Automobile Industry of Krishnagiri District - Santhoshkumar, R; Rajasekar, N (Journal of Commerce and Trade, 2011)
This research paper examines the applicability of Talent Management in Automobile Industry in Krishnagiri district. The primary data collected from the 100 different levels of employees in automobile industry. Hypothesis test used to measure the applicability of talent management. This paper found the executives feel that Talent Management is the competitive Advantage for the company; they believe that their company’s recruitment policy is leveraged towards recruiting top talent. This study helps the company to retain present talented workforce and stop them from quitting the organization. Critical Talent has been defined and identified at covering all staff level positions, suggestions have been proposed in line with company’s requirements and capabilities and to select the perfect and highly skilled employees for the organization. Key words: Talent management, retain, skilled, employees, applicability.